Fire Sales and Ex Ante Valuation of Systemic Risk: A Financial Equilibrium Networks Approach - Spiros Bougheas; Adam Hal Spencer (Center for Economic Studies and ifo Institute (CESifo), 2022)
We introduce endogenous fire sales into a simple network model. For any given initial distribution of shocks across the network, we develop a clearing algorithm to solve for the financial equilibrium. We then utilise the results to perform ex ante risk assessment and derive risk premia for every balance sheet item where liabilities are differentiated according to priority rights. We find that risk premia reflect both idiosyncratic risk and risk of contagion (network risk). Moreover, we show that network risk magnifies the gap between the risk premia of equity and debt. We also perform comparative statics, showing that changes to the distribution of shocks and network structure can have substantial effects on the level of systemic losses.
Keywords: G33; G32; D85; 330; networks; fire sales; systemic risk premia; risk assessment